The Interaction of Digital Technology and Literacy Practices in Nuosu Script, China - Walters, Susan (Journal of the Southeast Asian Linguistics Society)
Digital technology enables new forms of textual communications, linguistic creativity, and cultural empowerment for many local language communities (Li, Brar, and Roihan 2021). This study uncovers how Nuosu people, a thriving minority ethnic group in southwest China, choose to use digital technologies for reading and writing their traditional script. The data, part of a larger qualitative study that revealed how Nuosu people conceptualize and practice literacy (Walters 2021), were collected utilizing semi-structured interviews with 22 Nuosu adults. Findings show that the Nuosu primarily use digital language technologies for Nuosu literary and artistic expressions, which carry knowledge crucial to their identity. They also use these technologies for teaching and learning their script, not for interpersonal communication or majority-language domains. The use of digital Nuosu in literary domains aligns with their centuries-old practice in which religious specialists (bimo) use Nuosu script for ritual writings and preserving traditional oral literature in the form of epic poems and proverbs. The Nousu case suggests that literacy patterns once established are deeply held and not easily influenced by changes in modality.